Controlled Release of Drugs from Cellulosic Wound Bandage Using Silica Microsphere as Drug Encapsulator Module - Ahmed G. Hassabo, Amina L. Mohamed, Ahmed A. Nada, Nabil Y. Abou Zeid (Journal of Applied Pharmaceutical Science, 2015)
Controlled-drug-releasing materials show promising applications in medicinal bandages. In addition, one could incorporate drugs to make such bandages more versatile. During this context, silica microparticles were synthesized, during presence of different drugs namely sodium diclofenac, linoleic acid and recienoleic acid. The morphological characterization shows formation of monodispersed, silica microparticles. FT-IR spectroscopy provided the interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. UV–vis spectroscopy showed persistence of the different drugs signature, especially its R group, confirming its antimicrobial activity even after conjugation. Using zone-of-inhibition studies, the antimicrobial studies were done on two microorganisms, namely, Staphylococcus aureus and Escherichia coli. However, the encapsulator module showed controlled release of all drugs for the duration of 48 h. This work demonstrated an effective protocol to prepare antimicrobial patches for controlled drug delivery.
Keywords: Controlled-drug-releasing, silica microparticles, sodium diclofenac, linoleic acid and ricinoleic acid.